Quantificação de carbono e emissões de gases de efeito estufa sob diferentes tratamento do solo no cerrado brasileiro - Barreto, Renata da Costa (2009)
Currently, there is a global concern with the increase of greenhouse gases (GHGs) in the atmosphere due to its role in the rapid changes in energy balance. Practice change of land use are becoming more frequent, which may make it possible to increase or decrease in emissions of GHGs to the atmosphere. Studies on the quality of carbon (C) in soils and distribution of aggregates show features related to its accumulation in the soil. Since the measures soil respiration, carbon dioxide emissions (CO2), indicate the rate of oxidation of C. It is estimated that 70% of the Cerrado region is susceptible to agriculture, being 9 million hectares under notillage. The objective of this study was to evaluate and compare the effects of the operations and activities of farming, such as sowing and harvest on carbon storage in soil and net emissions of GHGs in two types of soil treatment (No-tillage, PD, and conventional tillage-PC) in an experiment located in Rio Verde, Goias, Brazilian Cerrado. The soil of the native forest was also evaluated by reference to agricultural areas. We evaluated the physical, chemical properties and the distribution of aggregates on soil, microbial biomass, carbon and nitrogen (N) storage, the emissions of CO2 and nitrous oxide (N2O) through-flow measurements (in situ) and laboratory incubations of bulk soil samples and soil aggregates. The results of mean weight diameter (MWD) showed a better aggregation of agricultural soils, indicating that the presence of the crop may have improved the quality of the soil, promoted the incorporation of soil organic matter (SOM). C stocks total CO2 emissions effectively equal in soils under CT and NT, the little difference in their states of aggregation and the absence of increased C stabilized the soil aggregates in NT indicate that this soil does not respond well to the NT in terms of accumulation and preservation of C. The N2O emissions and N stocks were also evaluated. In addition to lower emissions of N2O in soils under NT and CT, the soil under native forest in Rio Verde also had low emissions, even immediately after rain events, suggesting that the soil in the region have little tendency to emit N2O. The largest stock of N was observed in aggregates of soil under CT, but these values were not reflected in the analysis of the stock of total nitrogen.